Absence of SARS-CoV-2 antibodies in pre-pandemic plasma from children and adults in Vietnam. (October 2021) - Chau, Nguyen Van Vinh; Nhan, Le Nguyen Thanh; Nguyet, Lam Anh; Tu, Nguyen Thi Kha; Hong, Nguyen Thi Thu; Man, Dinh Nguyen Huy; Ty, Dinh Thi Bich; Nhu, Le Nguyen Truc; Yen, Lam Minh; Khanh, Truong Huu; Quy, Du Tuan; Minh, Ngo Ngoc Quang; et al.
Abstract: We tested pre-pandemic (2015–-2019) plasma samples from 148 Vietnamese children and 100 Vietnamese adults at high risk of zoonotic infections for antibodies against SARS-CoV-2 nucleocapsid and spike proteins. None was positive. The data thus demonstrated no evidence of prior serological cross-reactivity with SARS-CoV-2 that might explain the low numbers of COVID-19 in Vietnam. No pre-existing cross-reactivity might explain Vietnam success of COVID-19 control.